Improving Learning Outcomes of PAI & BP Class IV Students of SD Negeri 11 Kepenuhan on the Material "Aku Anak Sholeh" Through Assignment and Resitation - Suanto, Suanto; Nurwahidah, Nurwahidah; Nasution, Zainul Mahdi (Indonesian Journal of Basic Education, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) and Budi Pekerti (BP) of fourth grade students of SD Negeri 11 Kepenuhan on the material "Aku Anak Sholeh" through assignment and resitation. This study used a Classroom Action Research (PTK) approach with 59 students as research subjects. The methods used included independent assignments at home and in-class recitation, which aimed to encourage students to be more active in learning and internalising the material that had been taught. The results showed a significant improvement in students' learning outcomes, both in knowledge and attitude aspects, after the implementation of this action.